Impact of Graft Selection on Donor and Recipient Outcomes After Living Donor Liver Transplantation. Issue 6 (June 2016) - Braun, Hillary J.; Dodge, Jennifer L.; Roll, Garrett R.; Freise, Chris E.; Ascher, Nancy L.; Roberts, John P.
Abstract : Background: Balancing donor and recipient risks in living donor liver transplantation remains an issue of debate. This study assessed the impact of graft selection on outcomes and complications for left lobe (LL) versus right lobe (RL) donors and recipients. Methods: The medical records of donors and recipients, who underwent living donor liver transplantation at our institution between 2003 and 2015, were reviewed. For donors, we evaluated graft volume, residual liver volume per standard liver volume, length of hospital stay (LOS), complications, and readmissions. For recipients, we looked at graft and patient survival, graft function at postoperative days 7 and 14, graft volume, LOS, biliary complications, Model for End-Stage Liver Disease at transplant, and hepatitis C virus status. Results: At 5 years posttransplant, there were no significant differences in graft survival for LL recipients (86% [95% confidence interval, 74-93]) compared with 82% (95% confidence interval, 69-89) for RL recipients ( P = 0.85) or recipient survival (90% vs 84%; P = 0.44). In LL recipients, postoperative days 7 and 14 median international normalized ratio (1.5 and 1.2, respectively) and total bilirubin (4.6 and 2.7) were significantly greater compared with RL recipients (7 and 14 days international normalized ratio [1.2, P < 0.001; 1.1, P = 0.001] and total bilirubin (2.7, P = 0.001; 2.1, P = 0.05)). The LL recipients also had a significantly greater median LOS (14 vs 10, P = 0.008). Median donor LOS was significantly greater for RL donors (7 [interquartile range, 7-8] vs 7 [interquartile range, 6-7] days, P < 0.001). Conclusions: The RL and LL grafts provide comparable long-term outcomes in properly selected donor-recipient pairs and the appropriate use of LL grafts does not impact graft or patient survival at 5 years posttransplant. Abstract : Right lobe and left lobe grafts in living donor liver transplantation provide comparable long-term outcomes in properly selected donor-recipient pairs, and the appropriate use of left lobe grafts does not impact graft or patient survival at 5 years posttransplant.